Nigeria : Staff Report for the 2013 Article IV Consultation. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
This 2013 Article IV Consultation highlights Nigeria's poverty and income inequality that remain high and social and governance indicators that are below averages for sub-Saharan Africa. Growth is expected to remain strong, driven by agriculture, trade, and services. Inflation should continue to decline, in line with a tight monetary policy, and a lowering trend in food prices from higher rice and wheat production. Transparency and governance in the oil sector should be enhanced, including by strengthening the regulatory framework through the passage of a sound Petroleum Industry Bill featuring stringent enforcement clauses.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet